Delocalization Process, Coping Mechanisms and Psychosocial Wellbeing of Public Secondary School Principals in Selected Counties in Eastern Region, Kenya - Stephen, Munyiri; John, Ogembo; Susan, Kinyua (Advances in Social Sciences Research Journal, 2022)
The study was informed by the need to contribute in bridging the existing knowledge gap with regard to the relationship between delocalisation process, coping mechanisms and psychosocial wellbeing of delocalised Principals. Since inception of implementation of delocalisation of teachers by the Teachers Service Commission in Kenya, there has been increasing call for suspension or total scrapping of the policy. The call has been attributed to the perceived adverse effects of the policy on Principals wellbeing and ultimately the school communities. However, lack of empirical data on the extent to which implementation of the policy impacts the Principals limits discourse, thus the need of this study. A descriptive cross sectional survey study in which 277 delocalised Principals, 12 Education officials and 18 Union officials participated by answering self-report questionnaires. Data obtained was analysed descriptively and inferentially. Findings showed a significant relationship between delocalisation process and psychosocial wellbeing of the delocalised Principals. The study also established that involvement of the delocalised Principals in religious activities; physical activities and seeking medical attention have a significant influence in the relationship between implementation of delocalisation and psychosocial wellbeing. It is therefore recommended that utilisation of such mechanisms be enhanced to better help the Principals cope.